Low intensity conflicts : - Raza, M. Maroof (Kartikeya Publications, 1995)
This book introduce about: Low intensity conflicts, review of contemporary India military commitments in Low-Intensity conflicts, Politico-Military policy imperativess for an India faced with the proliferation of Low-Intensity conflicts.